Lógicas vivenciais da identidade extensionista em uma organização pública de extensão rural - Souza, Leliani Valéria de (2011)
This dissertation seeks to analyze and understand the process of identification and construction of professional identity from the perspective of rural extension workers, and the influence of public agricultural extension in this context. For this study are the concepts of identity, professional identity and organizational identification. The research is based on a case study scenario that has a public extension of the state of Santa Catarina. 22 interviews were conducted, 21 with extension officers based in rural municipalities distributed in eight regions of the state and a director of the extension o the organization studied. The analysis focuses on the experiential logic of identity extension, rural extension workers in identifying with the organization and job satisfaction. The results show the definition of three extension profiles: the company-oriented, self-focused and guided by an ideal, which have an undeniable consistency in its configuration, the result of a dual transaction, one between the individual and his past, and the other between the individual and the organization built through processes of socialization diverse and differentiated. It appears that there are several factors that influence the identification of rural extension workers with the company, which showed very high degree. It was also noted that the rural extension wants to be recognized internally by their performance and dedication as well as have effective career advancement prospects. Finally, the so-called identity crisis is not recognized by all respondents, and acquires different meanings. For some this may be the breakdown of traditional values and references hitherto accepted as guiding the lives of these professionals, which induces changes in the mental constructs associated with identity previously built.